2011
DOI: 10.1080/15459624.2011.617250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sampling Methods for Measuring Exposure to Volatile Inorganic Acids in Workplace Air. Part 2: Sampling Capacity and Breakthrough Tests for Sodium Carbonate-Impregnated Filters

Abstract: In France, the MétroPol 009 method used to measure workplace exposure to inorganic acids, such as HF, HCl, and HNO3, consists of a closed-face cassette fitted with a prefilter to collect particles, and two sodium carbonate-impregnated filters to collect acid vapor. This method was compared with other European methods during the development of a three-part standard (ISO 21438) on the determination of inorganic acids in workplace air by ion chromatography. Results of this work, presented in a companion paper, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The sampler has an entry nozzle of aluminium (diameter: 10 mm and length: 9 mm) and of the total length 7 mm is a polytetrafluoroethylene-sealed O-ring that protrudes out of the front of the filter holder. The sampler design indicated that it can be used for sampling the inhalable fraction of aerosol, for which 90% of the mass size distribution is below 20  μ m. Moreover, the backup Swinnex allowed 94% ± 8% (4 mg/m 3 ; sampling time: 480 min) HF retention, in accordance with that proposed by Demange et al, 2011 [29], OSHA methods n. 21 [30], and PV2024 [31]. Desorption with 1.0 mL of 0.5 M phosphate buffer (pH 6.8) allowed a 98% recovery of fluoride from MCE filters impregnated with sodium carbonate (mean recovery of the spiked sodium fluoride).…”
Section: Resultssupporting
confidence: 74%
“…The sampler has an entry nozzle of aluminium (diameter: 10 mm and length: 9 mm) and of the total length 7 mm is a polytetrafluoroethylene-sealed O-ring that protrudes out of the front of the filter holder. The sampler design indicated that it can be used for sampling the inhalable fraction of aerosol, for which 90% of the mass size distribution is below 20  μ m. Moreover, the backup Swinnex allowed 94% ± 8% (4 mg/m 3 ; sampling time: 480 min) HF retention, in accordance with that proposed by Demange et al, 2011 [29], OSHA methods n. 21 [30], and PV2024 [31]. Desorption with 1.0 mL of 0.5 M phosphate buffer (pH 6.8) allowed a 98% recovery of fluoride from MCE filters impregnated with sodium carbonate (mean recovery of the spiked sodium fluoride).…”
Section: Resultssupporting
confidence: 74%
“…(11) The method has been independently verified for all three acids, (12) in accordance with applicable performance criteria. (10) An interlaboratory study with 5 participants found negligible biases and good agreement for HCl and HNO 3 at concentrations between 0.6 and 8 mg/m 3 for HCl and 0.8 and 10 mg/m 3 for HNO 3 . (13) Expanded method uncertainty estimates found were U < 12% for HCl and HBr and U <14% for HNO 3 .…”
Section: Niosh Methods 7907 For Volatile Acids: Hydrochloric Nitric Amentioning
confidence: 97%
“…(8) Also, no breakthrough of gaseous HF was observed from impregnated filters for up to 5 mg fluoride. (9,10) The component of the coefficient of variation of the method that arises from analytical variability, determined from the analysis of spiked filters, was 2.4% to 5.6% for HF and 1.7% to 3.3% for fluorides. (8,9) No effect of relative humidity (RH 20–80%) was observed on recovery of particulate fluoride over the concentration range of 0.3 – 5 mg/m 3 .…”
Section: Niosh Methods 7906 For Particulate Fluorides and Gaseous Hydrmentioning
confidence: 99%
See 1 more Smart Citation